Low dimensional semiconductor structures MOCVD growth and their characterizations - Song, Yi Fei. (2008)
This project is on low dimensional semiconductor structures MOCVD growth and their characterizations, mainly focused on multiple quantum wells structure growth by MOCVD. Samples were characterized by using high resolution X-ray diffractions (XRD) and photoluminescence (PL). In this dissertation, properties of low dimensional semiconductor quantum well structures have been discussed. The principle of MOCVD growth in terms of its growth process, mechanism, the starting precursors and growth system has been described. Experiment setup and the application of XRD and PL used in this project have been introduced.